A Comparative Evaluation of Landuse and Forest Type Classification and Mapping with Aerial photographs Vis-a-vis Conventional Ground Stock Mapping-a Case Study in Tehri Garhwal Himalayas - Tiwari, K. P. (Indian Forester, 1978)
Evaluation of effective mapping unit through a rational classification system and its accurate delineation are essential for an effective forest map. The paper describes the concept of evolving a suitable classification system and defining mapping units with its delineatoin through the use of medium scale Panchromatic aerial photographs for a forest area in Tehri Garhwal Himalayas. Comparative evaluation with the conventional ground stock map shows again upto two times in cost along with the increased effectivity.